Calorimetric testing of solar thermal absorbers for high vacuum flat panels. (1st September 2022) - D'Alessandro, Carmine; De Maio, Davide; Caldarelli, Antonio; Musto, Marilena; Di Giamberardino, Francesco; Monti, Matteo; Mundo, Teresa; Di Gennaro, Emiliano; Russo, Roberto; Palmieri, Vittorio G.
Highlights: Precise measurements of SSA optical properties are performed in operating condition. Indoor measurements (using LED) were verified with outdoor ones (sun illumination) Precise performance of SSA designed for high vacuum flat collectors can be assessed. Agreement with optical measurements is obtained only close to room temperature. Calorimetric measurements become more precise as temperature increases. Abstract: Among solar thermal collectors, the evacuated flat panel is emerging as a reference technology for operation at temperatures as high as 200 °C with an increased annual energy production owing to both direct and diffuse light capture. Accurate measurements of the optical properties of the selective absorbers used in such devices are key for a reliable estimation of the overall performance. These optical properties must be measured under high vacuum at high temperatures, conditions under which the panels are meant to operate. In this study, we accurately measured these properties using a calorimetric technique. The measurement procedure is based on a power balance equation for a flat sample absorber suspended in a high-vacuum chamber with minimized thermal losses and is well adapted for this class of devices. Calorimetric measurements obtained under Sun and LED light illumination revealed excellent reproducibility and good agreement with those obtained using traditional optical analysis at low temperatures in air. When extended up to the absorber stagnation temperature, which often exceeds 300 °C, the calorimetric measurements started to deviate from the optical measurements, indicating the importance of measuring under actual operating conditions.